STRATEGI PEMERINTAH DESA BULANG DALAM MENGANGKAT UMKM KLEPON: MENGGALI POTENSI LOKAL UNTUK KEMAJUAN EKONOMI - Rochman, Arif; Muhaimim, Hikmah; suprapto, suprapto (Universitas Islam Majapahit, Indonesia, 2024)
Community empowerment is a strategy carried out to achieve long-term socio-economic independence of the community. Community empowerment through Micro, Small, and Medium Enterprises (MSMEs) is the main agenda. In the midst of economic challenges and global developments. This study aims to determine the Government's Strategy in Encouraging Community Empowerment Through Klepon MSMEs in Bulang Village, Prambon District, Sidoarjo Regency. The method in this study is to use a quasi-qualitative approach (qualitative research) using a case study used in this study. The strategy for empowering Klepon MSMEs in Bulang Village shows that the integration between local initiatives and village government support can have a significant positive impact on the local economy, that the Bulang Village Government, Prambon District, Sidoarjo Regency, is actively involved in supporting the empowerment of Klepon MSMEs. In this case, the five empowerment approaches are enabling, empowering, protecting, supporting, and sustaining. Overall, these approaches are used as a basis for designing a comprehensive strategy to improve the performance and sustainability of Klepon MSMEs. Through the application of these approaches